1999
DOI: 10.1111/j.1528-1157.1999.tb00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Postoperative Seizure Control by Hippocampal Event‐Related Potentials

Abstract: Summary:Purpose: In spite of unequivocal results of the presurgical evaluation, between 10 and 30% of patients with medial temporal lobe epilepsy (MTLE) do not become seizure free by temporal lobe surgery. Because event-related potentials (ERPs) recorded within the hippocampal formation have been shown to be sensitive to the epileptogenic process, we examined whether ERPs can help to improve the prediction of postoperative seizure control.Merhods: We recorded ERPs to words from bilateral intrahippocampal elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 22 publications
3
27
0
1
Order By: Relevance
“…Slopes were more negative in the controls than the patients. Furthermore, using hippocampal depth electrodes in patients with temporal lobe epilepsy, Grunwald et al (1999) found that medial temporal N400 responses to items decreased with repetition in the intact hippocampus but not in the epileptic hippocampus. These data suggest that an economic use of learning-related neural resources characterizes a well functioning memory system.…”
Section: Discussionmentioning
confidence: 96%
“…Slopes were more negative in the controls than the patients. Furthermore, using hippocampal depth electrodes in patients with temporal lobe epilepsy, Grunwald et al (1999) found that medial temporal N400 responses to items decreased with repetition in the intact hippocampus but not in the epileptic hippocampus. These data suggest that an economic use of learning-related neural resources characterizes a well functioning memory system.…”
Section: Discussionmentioning
confidence: 96%
“…Our findings thus show that separate analysis of event-related power and phase effects can reveal additional information compared with conventional ERP evaluation. The averaged AMTL-N400 recorded from within the rhinal cortex showed a newminus-old repetition effect (Smith et al, 1986;Nobre and McCarthy, 1995;Grunwald et al, 1998aGrunwald et al, , 1999) which would Power/phase modulation in the rhinal cortex (upper row) and hippocampus (lower row) for hits (correctly identified repeated words; left) and correct rejections (correctly identified new words; right) in a continuous recognition paradigm (grand average). The plots show color-coded synchronization values between the mean-wavelet phases (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Because seizure onset could not be determined unequivocally by noninvasive investigations, electrodes were implanted according to clinical requirements. The ERP investigation, employing a continuous visual word recognition paradigm [Rugg and Nagy, 1989], is part of our presurgical work-up, providing predictors of seizure control and verbal memory performance after temporal lobe surgery [Grunwald et al, 1998b;1999a]. All patients were right hand dominant (selfreported) and native German speakers.…”
Section: Patientsmentioning
confidence: 99%